Wpływ wybranych czynników psychospołecznych na proces podejmowania decyzji kredytowych w banku - Kowalczyk, Elżbieta (Wydział Prawa i Administracji UAM, 1996)
Economic transformations taking place in Poland after 1989 did not avoid such a branch of services as banking business. One of the most important alements to shape a new friendly to a client image of a bank is that of improving the quality of serving him and of reacting promptly to newly emerged needs. Within the process being object of attention in this paper the influence of both psychological and social factors is more and more appreciated. The action of factors mentioned modifies the final shape of decisions to be taken and both of them help to establish mutual contact between the bank clerk and his client as well as to fix up the image of a bank. The author discusses chosen psychological and social factors and characterizes their influence on the process of crediting decisions making in a bank. The author assumes that an evaluation of credibility of a banks' credit clients is a fundamental element in the analysis of decision within the process of crediting someone. Then follows brief characteristic of the process of such a decision analysis relating to an evaluation of crediting capacity with special stress on its personal aspect. Basic assumption here is a constatation that every client of a bank is perceived from threefold perspective by an employee of financing institution: - his own perspective, - perspective of a client himself, - perspective from surrounding circumstances. The element froming proper optics of a bank employee is the impact of importance of the first contact on the course of decision making in crediting process. The optics of a client himself is characterized with factors relating to organization of interpersonal contact between a bank clerk and the client of financins institution. We can find next a discussion of consequences of different space perceiving by interlocutors and some principles for psychological attempt to describe the organization itself of such a négociation.The optict of a bank clerks' surrounding influencing the quality of decision making process has been described through the effects and actions of a bank. The author focuses here on the process of shaping the attitudes of bank managers towards a client and also - in relation with a bank otself. The final part of the paper is devoted to personality features that influence the decision making process. Are considered as being significant: - stress resistance, - assertiveness, - feeling of the control well placed. Summing up the author draws the attention to the fact that bank clerks are generally deprived of psychological competences adequate to fully use the potential being inherent in psychological and social factors modelling the decision making process in a bank. Usuallu professionals are not hired to help enriching the process of evaluation of a firm with psychological and social aspects.
Influence of chosen psychological and social factors on the decision making procerss in credit bank